Analysis of The Factors That Contribute To The High Rate of Private Vehicle Ownership In DKI Jakarta - Lode Wijk Pandapotan Girsang (Universitas Sumatera Utara, 2023)
One of the primary causes of traffic jams in Daerah Khusus Ibu kota (DKI) Jakarta is the high number of private vehicle ownership. The DKI Jakarta government has implemented a number of measures to reduce motorized vehicles, such as the